Caricature – fun, art and scientific contribution - Todić Jakšić, Tijana R.; Jevremović, Jelena D. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
The paper aims to point out on various understandings of the term caricature. Then, we are going to show caricature’s place and importance at the time of its origin to this very day. Answering on questions and giving scientific conclusions concerning caricature’s usage as stimuli will be also dealt with. This paper will reveal caricature’s characteristics as an artistic form which weren’t appreciated until now. Origins and development of Serbian satirical press has also been surveyed.